Digital Financial Literacy and Fintech Publication Trends - Yuliana Subastine; Sisca Dian Rahmawati; Qisthoni Permatasari; Lamidi (ITB AAS Indonesia Surakarta, 2026)
The rapid digital transformation of the financial sector has intensified the need for strong Digital Financial Literacy (DFL) to ensure secure and inclusive participation in the fintech ecosystem. This study provides a comprehensive bibliometric analysis of global scientific publications on Digital Financial Literacy and financial technology ( fintech) from 2020 to 2025. Using 214 Scopus-indexed journal articles, the study maps publication trends, leading journals, influential authors, dominant research themes, and collaborative networks. The findings reveal a significant surge in publications beginning in 2023, driven by increased fintech adoption and the urgency of addressing digital financial risks. Economics, business, and Social Sciences emerge as the core disciplinary contributors, with China, India, and Indonesia leading global research output. Keyword co-occurrence and thematic mapping show concentrated attention on financial inclusion, technology adoption, digital finance, and emerging topics such as machine learning and cybersecurity. The study concludes that DFL is not merely a technical competency but a critical foundation for strengthening financial resilience, promoting inclusion, and mitigating risks associated with digitalization. Recommendations include integrating mixed-method approaches in future studies, expanding cross-regional collaborations, and prioritizing ethical, contextual, and inclusive digital financial education frameworks.